2022
DOI: 10.3389/fimmu.2022.964398
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of convalescent plasma in COVID-19 patients: A systematic review and meta-analysis of randomized controlled clinical trials

Abstract: The objective of this study was to assess whether convalescent plasma therapy could offer survival advantages for patients with novel coronavirus disease 2019 (COVID-19). An electronic search of Pubmed, Web of Science, Embase, Cochrane library and MedRxiv was performed from January 1st, 2020 to April 1st, 2022. We included studies containing patients with COVID-19 and treated with CCP. Data were independently extracted by two reviewers and synthesized with a random-effect analysis model. The primary outcome wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 93 publications
0
2
0
1
Order By: Relevance
“…Eine aktuelle Metaanalyse, in der 32 randomisierten Studien mit insgesamt 21478 behandelten Patienten berücksichtigt sind, gibt für die unselektierte Gesamtgruppe der CCP-behandelten Patienten eine Risikoratio für die Tag-28-Mortalität von 0,94 (95 % Konfidenzintervall: 0,87-1,02) an [4]. Studien, die eine späte CCP-Transfusion im Krankheitsverlauf bei unselektierten Patienten untersuchten, konnten in der Mehrzahl keine Wirksamkeit nachweisen [1,4]. In randomisierten und nicht randomisierten Studien zeigen sich Signale für die Wirksamkeit bei Patienten, welche mit einer hohen, kumulativen anti-SARS-CoV-2-Antikörpermenge behandelt werden (z.…”
Section: Die Datenlage Zur Wirksamkeit Von Ccp Scheint Inkonsistentunclassified
“…Eine aktuelle Metaanalyse, in der 32 randomisierten Studien mit insgesamt 21478 behandelten Patienten berücksichtigt sind, gibt für die unselektierte Gesamtgruppe der CCP-behandelten Patienten eine Risikoratio für die Tag-28-Mortalität von 0,94 (95 % Konfidenzintervall: 0,87-1,02) an [4]. Studien, die eine späte CCP-Transfusion im Krankheitsverlauf bei unselektierten Patienten untersuchten, konnten in der Mehrzahl keine Wirksamkeit nachweisen [1,4]. In randomisierten und nicht randomisierten Studien zeigen sich Signale für die Wirksamkeit bei Patienten, welche mit einer hohen, kumulativen anti-SARS-CoV-2-Antikörpermenge behandelt werden (z.…”
Section: Die Datenlage Zur Wirksamkeit Von Ccp Scheint Inkonsistentunclassified
“…Even if it was seen as a promising strategy, the administration of plasma from convalescent patients, the hyperimmune plasma, did not exert any significant reduction in mortality and had minor impact on clinical improvement in individuals with moderate to severe disease [ 79 ]. A Chinese meta-analysis study [ 80 ] described that, in 32 randomized controlled trials and 21,478 patients, convalescent plasma therapy was not associated with significantly reduced 28-day mortality in COVID-19 patients, and it was not related to improvements in other survival outcomes (length of hospitalization, time without respiratory support, risk of symptoms progression, and requirement of mechanical ventilation). Moreover, in terms of safety, the treatment presented a trend with no statistical significance of higher incidence of adverse events, suggesting that the treatment could be recommended only in the context of clinical trials for severe COVID-19 patients, due to limited suppressive effect on inflammation and no significantly improved clinical outcomes [ 80 ].…”
Section: From the First State Of Emergency To The Current Standard Tr...mentioning
confidence: 99%
“…It was also postulated that these patients could be potential donors of convalescent plasma, which was theorized to be a life-saving therapy. Unfortunately, meta-analyses have shown that convalescent plasma is not an optimal treatment choice for COVID-19 [5,6].…”
Section: Introductionmentioning
confidence: 99%